The Development of Musical Taste in Children - Bojnec, Iva (Širjenje obzorij o poučevanju glasbe, 2025)
The aim of this chapter is to explore in depth the development of musical taste and preferences in children. The research begins in the prenatal period, progresses through early childhood, and continues into adolescence. A significant focus is placed on the development of musical taste during the preschool period. Primary socialization, particularly the influence of the child's family and caregivers, plays a crucial role in this process. The results of various studies confirm that the family has the greatest impact on shaping an individual's musical taste.